The Sour Grape - John, Jory (New York : Harper, an imprint of HarperCollinsPublishers, 2022)
"The Sour Grape holds grudges for every reason under the sun. Lime never returned a scarf they borrowed? Grudge! Orange never called back? Grudge! But when a friend holds a grudge against the Sour Grape without listening to an explanation, the Sour Grape realizes how unfair grudges can be. Could a bunch of forgiveness and compassion be enough to turn a sour grape sweet?"--
Keywords: Self-esteem -- Juvenile fiction; Etiquette -- Juvenile fiction; Emotions -- Juvenile fiction; Self-esteem -- Fiction; Etiquette -- Fiction; Emotions -- Fiction; Picture books